2017
DOI: 10.1016/j.pcl.2017.03.009
|View full text |Cite
|
Sign up to set email alerts
|

Pediatric Human Immunodeficiency Virus Continuum of Care

Abstract: SYNOPSIS Children and adolescents living with HIV represent a distinct population that requires a unique approach to HIV care. Prevention, testing, initiation of antiretroviral therapy (ART), and retention and engagement in care are all critical steps in the care of these youth. Each step requires providers to address age-specific barriers, so that successful and prolonged viral suppression can occur. Adherence to ART, disclosure of HIV-positive status, and stigma are all examples of struggles faced by youth, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 32 publications
0
5
0
Order By: Relevance
“…Other factors, such as medication formulation, frequency of dosing, drug toxicities and their side effects, developmental stage as well as psycho-social, behavioral, and socio-demographic characteristics of adolescents, have been associated with non-adherence to ART. However, no consistent predictors of either good or poor adherence in adolescents have been identified [39][40][41], thereby posing a threat to adolescents' adherence during crisis, such as the COVID-19 pandemic. Several studies have demonstrated that adherence is not static, and can fluctuate with time on treatment [42].…”
Section: Other Challenges Of Art Adherencementioning
confidence: 99%
“…Other factors, such as medication formulation, frequency of dosing, drug toxicities and their side effects, developmental stage as well as psycho-social, behavioral, and socio-demographic characteristics of adolescents, have been associated with non-adherence to ART. However, no consistent predictors of either good or poor adherence in adolescents have been identified [39][40][41], thereby posing a threat to adolescents' adherence during crisis, such as the COVID-19 pandemic. Several studies have demonstrated that adherence is not static, and can fluctuate with time on treatment [42].…”
Section: Other Challenges Of Art Adherencementioning
confidence: 99%
“…Progress towards elimination of pediatric HIV and planning of health services and provision of ART in many high burden countries is hampered by the lack of resources to report robust age-specific data [3]. Past estimates of rates of MTCT and numbers of CWH have been generated from health facility data and mathematically modeled projections [4,5].…”
Section: Introductionmentioning
confidence: 99%
“…death of parents due to AIDS, suicide risk; Dako-Gyeke et al, 2020; Lall et al, 2015) and mental health problems like depression and anxiety (Dessauvagie et al, 2020; Too et al, 2021). Previous research has found a bidirectional association between depression and ART adherence (Benton et al, 2019) and a relationship between anxiety and notification of diagnosis, which in turn involves stigma and fear of rejection (Chandwani et al, 2012; Gray et al, 2017).…”
Section: Introductionmentioning
confidence: 99%